Estimation of Caffeine in Different Marketed Samples of Tea - Gogate, Shweta; Mathur, Rahul; Mathur, Adarsh; Hukre, Adarsh; Rehman, Abdur; Hussain, Afzal; Rathi, Jagdish (Asian Journal of Pharmaceutical Research and Development, 2022)
The objective of this study was estimate of Caffeine in Different Marketed Samples of Tea Although there were no significant differences between the orders of caffeine content among the tested tea brands, the method with chloroform isolation exhibited significantly lower results and the highest results obtained by the micromethod using H2SO4 at 273 nm UV wavelength with regard to other methods applied for the determination of caffeine. The non-laborious chemical method of determination of caffeine in tea samples using Lead oxide and Chloroform has shown us the caffeine levels in various samples. It is also true that caffeine in tea can have positive and negative effects on the organism consuming it.